(تحليل محتوى مقرر العروض الرياضية وفق تصنيف بلوم من وجهة نظر الطلبة) - معوض, وائل مارون (Latakia University Journal -Medical Sciences Series, 2013)
العروض الرياضية عبارة عن عملية توظيف مجالية الحركة في أشكال هندسية وفنية منظمة لذلك تدرّس في كليات التربية الرياضية /نظام ساعات معتمدة/ وأقسام الديكور والفنون الجميلة. وانسجاماً مع متطلبات الجودة والاعتمادية ومعايير (NARS) وتطبيقاً لمتطلبات العملية التدريسية والتعليمية تم إقامة هذا البحث للوقوف على واقع مقرر العروض الرياضية وطريقة تدريسه وجودة مفرداته. حيث يتم استبيان الطلاب وفق تصنيف بلوم بمستوياته الستة ضمن 33 سؤال بعد أن تم تقويم الاستبيان من 13 عضو هيئة تدريسية في كلية التربية الرياضية وكلية التربية للوصول إلى نتيجة أن طريقة التدريس المعتمدة تحقق أهداف المقرر, وأن مستوى الطلاب جيد بالنسبة لفهم المقرر. إضافة إلى كفاية مفردات المقرر لتشمل كل متطلبات العروض الرياضية. The sport shows is the use of field movement to form geometric and artistic shapes .So it taught at the physical education ,Decoration, and Fine arts faculties. This research is made to meet the requirements of quality, (NARS) standards ,and the needs of the teaching process and aimed to find out the state of the Sports Shows course , its methods and quality. A Questionnaire was conducted according to Bloom's Taxonomy with its six levels .the Questionnaire is consisted of 33 questions. The Questionnaire is evaluated by thirteen of the Faculty of Physical Education and Faculty of Education academic staff. to conclude that the applied teaching method achieves the course goals ,and the students comprehension level is good ,and the course items are adequate.